David C. Mearns papers - Mearns, David C. (David Chambers), 1899-1981.; Mearns, David C. (David Chambers), 1899-1981.; Mearns, David C. (David Chambers), 1899-1981.
Correspondence, writings, reports, and orders documenting Mearns's career as an official and historian of the Library of Congress and scholar of Abraham Lincoln. Includes drafts of Mearn's works, The Story up to Now; The Library of Congress, 1800-1946 (1947) and The Lincoln Papers; The Story of the Collection, with Selections to July 4, 1861 (1948). Correspondents include David M. Barkley, David Laurence Chambers, Jonathan Daniels, Charles E. Feinberg, Carl Haverlin, Harry Miller Lydenberg, Archibald MacLeish, Earl Schenck Miers, Ralph Geoffrey Newman, Carl Sandburg, Fred Schwengel, Alfred Whital Stern, Walter Trohan, and Justin G. Turner.
Selected material available through the Library of Congress Web site.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Librarian and historian. Assistant Librarian of Congress, chief of the Manuscript Division, superintendent of Reading Rooms, and director of the Reference Department.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barkley, David M., -- 1906-1983 -- Correspondence; Chambers, David Laurance, -- 1879-1963 -- Correspondence; Daniels, Jonathan, -- 1902-1981 -- Correspondence; Feinberg, Charles E., -- 1899-1988 -- Correspondence; Haverlin, Carl, -- 1899-1985 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lydenberg, Harry Miller, -- 1874-1960 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Miers, Earl Schenck, -- 1910-1972 -- Correspondence; Newman, Ralph Geoffrey, -- 1911- -- Correspondence; Sandburg, Carl, -- 1878-1967 -- Correspondence; Schwengel, Fred, -- 1907-1993 -- Correspondence; Stern, Alfred Whital, -- 1881-1960 -- Correspondence; Trohan, Walter, -- 1903- -- Correspondence; Turner, Justin G. -- Correspondence; Library of Congress; Library of Congress -- Officials and employees; Historians; Librarians